Problems Perceived by the Women Workers under MGNREGA in Jaipur District of Rajasthan - Gora, Annu Devi; Joshi, Madhuri (Indian Journal of Extension Education, 2017)
The present study was conducted in Jaipur District of Rajasthan, to find out the problems perceived by women workers in  MGNREGAin 2016. For this, 120 MNREGAwomen workers were selected and information was collected with the help  of structured interview schedule and data were analysed with the appropriate statistical tools. The major problems  perceived by the women workers were lack of time to care the children in the home, undue delay in getting the job card and  poor access to drinking water at work site.
Keywords: MGNREGA; jaipur district; rajasthan and women workers